Tawaduk Santri In Nusantara Cultural Perspective: A Multi-Discourse Analysis - Khusnul Khotimah; Wevi Lutfitasari; Maulid Taembo; Mohammad Hipni (El Harakah)
The pesantren tradition is a vital aspect of Nusantara culture that shapes students' humility in both religious and cultural practices. This humility (tawaduk) is expressed through distinct attitudes and activities. This study aims to present symbols of students' humility within Nusantara cultural practices and explore the ecological aspects of the unique pesantren culture as portrayed in mass media. This qualitative research utilizes a discourse analysis framework. In mass media discourse, symbols of students' humility are reflected in socio-cultural dimensions through cultural practices such as "cocoghen" rituals, Quranic study sessions ("ngaji kitab"), welcoming the night of Eid al-Adha, seclusion ("khalwat"), and communal meals ("mayoran"). These practices honor Prophet Muhammad, instill noble ethics, foster Islamic brotherhood (ukhuwah islamiyah), encourage surrender to Allah, and promote restraint from worldly desires. Additionally, the pesantren cultural practices serve as environments that preserve local customs, shape students' character, foster brotherhood, offer experiential learning, impart life values, and cultivate self-restraint. The finding of this research provides distinctive insights into the practices of local pesantren traditions, serving as a foundation for the development of the unique cultural heritage of the archipelago.